The NISWATHI Coaching Model for the Social and Personality Competence of Science Teachers: Bibliometric Analysis 2016-2025 - Ni Nengah Sri Swathi Nengah; A Wahab Jufri; AA Sukarso; I Putu Artayasa; Joni Rokhmat (Postgraduate Program, University of Mataram, 2025)
Science education plays a strategic role in developing students’ critical and analytical thinking skills, as well as fostering scientific attitudes. However, challenges in classroom management and the limited social and personality competencies of teachers often hinder the effectiveness of science learning. This study aims to analyze the research trends on the application of the NISWATHI Coaching Model in improving the social and personality competencies of science teachers from 2016 to 2025. A descriptive-analytical approach with bibliometric methods was employed, analyzing 1,000 documents indexed in Google Scholar and Dimensions.ai. Data were processed using VOSviewer to map relationships among keywords, authors, and institutions. The findings indicate a significant increase in publications related to the NISWATHI model, peaking in 2022 before slightly declining in subsequent years. Most publications appeared as book chapters and edited volumes, reflecting a conceptual and reflective approach to the model’s development. Bibliometric visualization revealed seven major research clusters, including teacher training, instructional innovation, leadership, and adaptation to educational crises such as the Covid-19 pandemic. Keywords such as digital transformation, holistic development, and future teacher emphasize the relevance of technology integration and comprehensive teacher development. These findings strengthen the position of the NISWATHI Coaching Model as a transformative and adaptive approach to enhancing teachers’ personality and social competence. The model not only focuses on pedagogical improvement but also on shaping reflective, collaborative, and responsive teacher character aligned with the demands of 21st-century education.